Changing principals' leadership through feedback and coaching. Issue 5 (29th July 2014) - Tobias Feldhoff, Professor Falk Radisch and Dr Eckhard Klieme, Professor; Goff, Peter; Edward Guthrie, J.; Goldring, Ellen; Bickman, Leonard
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – In this study the authors use longitudinal data from a randomized experiment to investigate the impact of a feedback and coaching intervention on principals' leadership behaviors. The paper aims to discuss these issues. Design/methodology/approach – In total, 52 elementary and middle school principals (26 receiving teacher feedback, 26 receiving feedback and coaching) were randomized into a year-long feedback and coaching study. Measures of leadership actions were collected from principals and teachers during the fall, winter, and spring. The authors use instrumental variables approach to examine the impact of treatment. Findings – Behavioral change may take longer than is presented in this study, which implies that these findings represent a lower-bound. As an intervention leadership coaching is costly and this research does not explore alternatives to help principals make feedback data actionable. Practical implications – It is unlikely that providing school leaders with feedback alone will induce behavioral change. Other systems and supports – such as leadership coaching – are needed to help principals make sense of feedback data and translate data into actionable behaviors. Originality/value – Few leadership studies use exogenous variation in treatment conditions to examine leadership outcomes. This study builds upon our causal knowledge of leadership behaviors and presents a viable intervention to improve school leadership.